The flag and the cross White Christian nationalism and the threat to American democracy - Gorski, Philip S. 1963-; Perry, Samuel L. (Oxford University Press, 2022)
In this short primer, Gorski and Perry explain what white Christian nationalism is and is not; when it first emerged and how it has changed; where it's headed and why it threatens democracy. Tracing the development of this ideology over the course of three centuries - and especially its influence over the last three decades - they show how White Christian nationalism motivates the anti-democratic, authoritarian, and violent impulses on display in our current political moment.
Keywords: Demokratie; Christ; Nationalismus; USA; Christianity and politics / United States; White nationalism / United States; Nationalism / Religious aspects / United States; United States / Politics and government / 21st century; United States / Religious life and customs